2020
DOI: 10.1016/j.ajhg.2020.08.018
|View full text |Cite
|
Sign up to set email alerts
|

De Novo and Inherited Variants in GBF1 are Associated with Axonal Neuropathy Caused by Golgi Fragmentation

Abstract: Distal hereditary motor neuropathies (HMNs) and axonal Charcot-Marie-Tooth neuropathy (CMT2) are clinically and genetically heterogeneous diseases characterized primarily by motor neuron degeneration and distal weakness. The genetic cause for about half of the individuals affected by HMN/CMT2 remains unknown. Here, we report the identification of pathogenic variants in GBF1 (Golgi brefeldin A-resistant guanine nucleotide exchange factor 1) in four unrelated families with individuals affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 79 publications
0
9
0
1
Order By: Relevance
“…GBF1 is involved in the formation of COP-I vesicles, maintenance, and function of the Golgi. The pathogenic variants of GBF-1 are recently found in individuals affected by distal hereditary motor neuropathies (HMNs) and axonal Charcot-Marie-Tooth neuropathy (CMT2) ( 61 ). It is tempting to speculate that STING is constitutively activated in these neurodegenerative diseases, as in the COPA syndrome, contributing in part to their pathogenesis.…”
Section: Retrograde Membrane Traffic Of Sting From the Golgimentioning
confidence: 99%
“…GBF1 is involved in the formation of COP-I vesicles, maintenance, and function of the Golgi. The pathogenic variants of GBF-1 are recently found in individuals affected by distal hereditary motor neuropathies (HMNs) and axonal Charcot-Marie-Tooth neuropathy (CMT2) ( 61 ). It is tempting to speculate that STING is constitutively activated in these neurodegenerative diseases, as in the COPA syndrome, contributing in part to their pathogenesis.…”
Section: Retrograde Membrane Traffic Of Sting From the Golgimentioning
confidence: 99%
“…Thus, in addition to directly acting on vesicular transport in the early secretory pathway, GBF1 also has a significant impact on maintaining the structural integrity and dynamic alteration of the Golgi apparatus ( Magliozzi et al, 2018 ). Furthermore, emerging evidence has revealed that GBF1 regulated different cycles of RNA replication in several virus families ( Martínez and Arias, 2020 ), participated in mitochondrial migration and localization ( Ackema et al, 2014 ), and affected the occurrence and development of neurodegenerative diseases ( Mendoza-Ferreira et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, heterozygous G-to-A substitution at position 877 in exon 10 of COL6A1 triggers the production of an altered extracellular collagen VI network that subsequently triggers the phosphorylation of the collagen VI receptor CMG2, an accumulation of endosomes and lysosomes and altered mitochondria and Golgi apparatus morphology in human fibroblasts. It has become clear that the ECM has profound effects on many cellular processes [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Consequently, this work exploits the opportunity to provide clinicians with novel diagnostic tools for monitoring and treating neuromuscular disorders.…”
Section: Discussionmentioning
confidence: 99%